Kepastian Hukum Status Tanah Ulayat Yang Dijadikan Hak Guna Usaha Setelah Habis Masa Berlakunya - Karani, Pasnelyza; Khairani, Khairani (Nagari Law Review, 2025)
The According to the provisions of Article 28 paragraph (1) of the Basic Agrarian Law, "Utilization rights are the right to cultivate land that is directly controlled by the state for a certain period of time for agricultural, fishing or livestock businesses." The subject of Cultivation Rights (HGU) in article 30 UUPA Junto Article 2 Government Regulation Number 40 of 1996 stipulates that those who can have Cultivation Rights Are Indonesian citizens and legal entities established according to Indonesian law and domiciled in Indonesia. Nowadays, HGU issues often involve the existence of customary land as a forum for the HGU to take place. The law has set a time limit for the use of HGU, but in reality when the HGU has expired, it is not uncommon for conflicts of interest to occur between customary land owners and HGU holders. Therefore, this research will examine the Legal Certainty of the Status of Ulayat Land which is Used as Cultivation Rights After the Validity Period Expires, to find out what the ideal legal parameters are to resolve this legal issue.